Implementation of The Pancasila Profile Students Project (P5) in Senior High Schools/Madrasah Aliyah in Berau Regency - Bella Dinda Septania; Aisyah Trees Sandy (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2024)
This research aims to determine the implementation of the pancasila profile students project (P5) senior high schools/madrasah aliyah in Berau Regency .This research uses descriptive quantitative methods. The population in this study were students in class X and XI. The data collection techniques for this research are observation, interviews and documentation. The results of the implementation of P5 activities with the theme of a sustainable lifestyle include projects for planting medicinal plants and vegetables, biopore absorption holes, compost fertilizer, crafts from plastic waste and campaigns zero waste. P5 activities with the theme of local wisdom highlight Berau culture with the Berau cultural festival activity project – Banua and making typical Berau Rutun batik.